The Practice of Portage in the Early Modern North Atlantic: Introduction to an Issue in Maritime Historical Anthropology - Pope, Peter (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractIn some respects, we know more about the anthropology of Amerindian groups in the early modern period than we do about the working European seamen with whom they interacted. We do know that negotiated wages or shares were but part of the economic culture of early modern mariners. Portage, also known in specific forms as “privilege” or “venture”, was a right European mariners once had to carry cargo, on their own account, for private sale. This hardly made them “merchants in the forecastle” but the practice of portage does make it difficult to accept, entirely, early modern mariners as a maritime proletariat. An examination of portage, both in the records of specific legal cases and in the body of maritime law, sheds some light on the historical anthropology of maritime life.